Introducing consensual criminal justice in Brazil - Gordilho, Heron José de Santana; Williams, Kenneth (Revista Brasileira de Direitos Fundamentais & Justiça, 2017)
This article of law review makes a comparative study between the criminal systems of Brazil and the USA. Using the functional method focusing on similarities between the criminal legal systems of Brazil and the United States. it first examines the North American system, which is based on popular participation in the administration of justice and the consensual truth. The article reviews the principles of due process and substantive legal process from judicial interpretations of the US Supreme Court. This system has allowed the US 95% of criminal trails are resolved through negotiation between prosecution and defense, which makes the system faster, efficient and democratic, for allowing the accused to participate in the decision on the criminal sanction that will be reckoned. Finally, the author criticizes the Brazilian legislation, which from the Act n. 9099/95 introduced the consensual truth in the Brazilian criminal system to crimes punishable by up to two years in prison. The article proposes the extension of this legal institute for any type of crime.